The “classifier” Category in Mandarin Chinese and Other Languages - Martínez, Consuelo Marco (Sinología hispánica. China Studies Review, 2020)
This paper contextualizes Mandarin Chinese within the general framework of the “classifier languages” of the world: Asian, Oceanic, Amerindian and African languages. It demonstrates that there are indeed many similarities among them, despite being geographically separated and not having any type of relationship. It continues analyzing the concept of "classifier" and the various types of classifiers in Chinese (individual, collective, partitive, temporary and standard or measure words), and comparing them with lexical and grammatical resources used in the Spanish language to express sense (recategorization) it resorts to some sort of "classifier". This paper demonstrates how “gender” in European languages is a grammar concept, semantically empty, so it should never be confused with a “classifier”. It recognizes how sometimes the overuse of classifier turns them into mere morphemes devoid of meaning, and other times keeps alive their semantic strength and continue denoting some perceived or imputed feature of the referent. This paper concludes by rejecting two widespread ideas: 1. The “primitivism” of classifier languages (against greater mental, logical and abstract development of the Indo-European languages). 2. The determinism in the categorization of the world and creation of a world view, as classifiers are conventional, with a strictly semantic role, but not cognitive nor deterministic.